PEMANFAATAN SANDEQ DALAM MENDUKUNG PENGEMBANGAN EKOWISATA BAHARI DI PULAU PASIR PUTIH KABUPATEN POLEWALI MANDAR - Manapa, Esther Sanda; Ukkas, Marzuki; Pasak, Hans Agung (Torani Journal of Fisheries and Marine Science, 2016)
Sandeq is a kind of marine transportation , since long has been operated by Mandar seaman and fishers alongthe coastal water area, as well as for fishing in Sulawesi Barat . This research was carried out to study thefeasibility of utilizing the Sandeq boat in marine ecotourism in Pasir Putih Island of the Polewali MandarRegency. SWOT Analisys has been applied to reveal the level of support of stakeholders regarding this idea, andthe strategies to be carried out in developing this specific ecotourism. The analysis shows that the internal andexternal factors are strongly support the program with a strong and aggressive manner and having a positifopportunity. A scenario on commercially operated ecotourism was designed and financially analyzed for 5 yearsperiod of operation: (1) Net present value of Rp 705.121.922,-, (2) Internal rate of returnof 100,99 %, and B/Cratio range from 1.7 at 3nd year to 3.7 at the 5th year. Those values showed that the project is financiallyfeasible. Three alternatives routes of marine ecotourism werw iidentified: (1) Ballanipa Village to KaramasangIsland, (2)From Balanipa Village to Battoa Island, (3) From Tonyaman Village to Karamasang Island and PasirPutih.Key words : Sandeq boat, ecotourism, Pasir Putih Island, Polewali mandar Regency, Swot Analysis, Financialanalysis.